2015
DOI: 10.1002/pros.22947
|View full text |Cite
|
Sign up to set email alerts
|

Significance of apoptotic and non‐apoptotic disseminated tumor cells in the bone marrow of patients with clinically localized prostate cancer

Abstract: In a single-centre cohort of patients with increased risk for disease recurrence, the presence of DTCs at the time of prostatectomy does not influence clinical outcome. For the first time in patients with PC, DTCs were evaluated for immunocytological features indicating apoptosis. Due to conflicting results of studies on DTCs, BM biopsies at time of radical prostatectomy cannot be recommended as a standard procedure in patients with clinically localized PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…[4] [5] [32] [33] There are no FDA-approved assays to detect DTCs, which make it difficult to standardize detection of PCa DTCs as the field attempts to determine the significance of disseminated cells at the time of primary therapy. [34] CTC systems are being adapted to isolate and detect DTCs in the BM. [24] Another technique used for the detection of DTCs is the reverse transcriptase polymerase chain reaction (RT-PCR) to detect PSA.…”
Section: Detection Of Circulating and Disseminated Tumor Cellsmentioning
confidence: 99%
“…[4] [5] [32] [33] There are no FDA-approved assays to detect DTCs, which make it difficult to standardize detection of PCa DTCs as the field attempts to determine the significance of disseminated cells at the time of primary therapy. [34] CTC systems are being adapted to isolate and detect DTCs in the BM. [24] Another technique used for the detection of DTCs is the reverse transcriptase polymerase chain reaction (RT-PCR) to detect PSA.…”
Section: Detection Of Circulating and Disseminated Tumor Cellsmentioning
confidence: 99%
“…Although various techniques such as TUNEL has been described, we used M30 to evaluate apoptotic index which was more simple and easy to perform (12). M30 is much more sensitive and specific for epithelial cells whereas TUNEL identifies all apoptotic cells in addition to epithelial lineage (19). Also M30 positivity comes out at an early stage of apoptosis and remains positive till to the necrosis of the tumor cells (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study reported detection of DTC in the bone marrow of PCa patients who have no evidence of disease (NED) for up to 18 years after surgery [6]. Controversies persist in whether the detection of PCa DTC pre- or post-surgery correlate with clinical parameters or outcomes, partly due to the lack of standardized methodologies to detect DTC [7,8]. In the past, detection and analysis of DTC has been limited by technology.…”
Section: Detection Of Dtcmentioning
confidence: 99%
“…This approach relied on the successful identification of DTC using epithelial markers including cytokeratin (CK) or epithelial cell adhesion molecule (EpCAM). A recent study by Todenhöfer et al summarized DTC studies that assessed the percentage of positive DTC detected in PCa patients pre- or post-surgery [8]. The rates of detection ranged from 13–45% using pan-CK staining [1,9,11,13,1722] and 72–90% using EpCAM staining [2,10].…”
Section: Detection Of Dtcmentioning
confidence: 99%